Conflict Consulting Clinic as a Method of Practical Training of Humanities Students - A. I. Strebkov; A. N. Sunami (Moscow Polytechnic University, 2021)
Conflictology as an educational program aimed at training specialists in the field of conflict resolution includes not only theoretical aspects, it is focused on modern practice. This stems both from the interdisciplinary subject field of conflict management, which combines the fundamental and applied components, as well as the needs of the labor market and the students themselves. At the same time, being in the circle of social sciences and humanities, conflict management faces the traditional challenges for this industry, associated with the most relevant forms of organizing students' practical work. The article analyzes the unique experience of the clinical form of organizing the practice of students majoring in conflictology, which has been implemented at St. Petersburg State University for 10 years. The practice of students, organized in the form of a conflict consulting clinic, first of all solves the problem of adapting students to the conditions and requirements of the practical activity of a conflictologist. The authors focus on the issues of correlating the clinical form to the requirements of the newest educational standard. The main forms and stages of students' work in the clinic are presented. The article describes the opportunities of students in acquiring the skills and abilities in conflict resolution, organizing and conducting the negotiation process, mastering conflict management strategies. The authors conclude that the conflict consulting clinic is a complex pedagogical methodology that includes both in-class and out-of-class forms of student practical activity in working with real cases based on client requests and promoting mediation, as well as teacher supervision with rhythmically organized discussion and correction of students' actions, which ensures due professionalism and quality services provided by students to external consumers.